2020
DOI: 10.21203/rs.2.21317/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitro Screening Antiviral Activity of Thai Medicinal Plants Against Porcine Reproductive and Respiratory Syndrome Virus

Abstract: Background Porcine reproductive and respiratory syndrome (PRRS) caused by the PRRS virus (PRRSV) results in economic losses in the swine industry globally. Several studies have investigated the use of plant extracts for the prevention and control of PRRS outbreaks. Thai medicinal plants may be useful for treating PRRSV infection in pigs. Therefore, we investigated the in vitro anti-PRRSV and antioxidant properties of seven Thai medicinal plants: Caesalpinia sappan Linn., Garcinia mangostana Linn., Houttuynia c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…However, WE exhibited lower activity than L‐ascorbic acid for DPPH scavenging activity of 5.77 times and for ABTS radical scavenging of 7.31 times. At the same time, the WE also lower activity than medicinal plant extract for DPPH, ABTS, and FRAP (Ruamrungsri et al ., 2016; Arjin et al ., 2020). For the reducing power, WE demonstrated the highest in antioxidant activity equal to 3.75 ± 0.11 µM Fe 2+ g −1 extract.…”
Section: Resultsmentioning
confidence: 99%
“…However, WE exhibited lower activity than L‐ascorbic acid for DPPH scavenging activity of 5.77 times and for ABTS radical scavenging of 7.31 times. At the same time, the WE also lower activity than medicinal plant extract for DPPH, ABTS, and FRAP (Ruamrungsri et al ., 2016; Arjin et al ., 2020). For the reducing power, WE demonstrated the highest in antioxidant activity equal to 3.75 ± 0.11 µM Fe 2+ g −1 extract.…”
Section: Resultsmentioning
confidence: 99%
“…As a part of our continuing search for naturally occurring potent Vpr inhibitors, we thus explored twelve Thai medicinal plants, Alpinia galangal ( rhizome ), Caesalpinia sappan (heartwood), Centella asiatica (aerials), Citrus hystrix (fruit peel), Garcina cowa (leaf), Garcina mangostana (fruit peels), Piper betel (leaf), Plumbago indica (roots), Punica granatum (fruit), Rhinacanthus nasutus (leaf), Senna tora (seeds) and Zingiber cassumunar (rhizome). Most of them have been used in the primary health care project in Thailand and by AIDS patients for the treatment of various viral diseases including HIV infection, and many studies have reported their antiviral activities [18–36] . As a result, we found potent anti‐Vpr activities in the ethanolic extracts of Punica granatum fruit, Centella asiatica aerials, and Citrus hystrix fruit peels.…”
Section: Introductionmentioning
confidence: 63%
“…17,18 Many researchers reported antiviral activity of mangosteen against chikungunya virus (CHIKV), porcine reproductive and respiratory syndrome virus (PRRSV), dengue virus (DENV), and avian pox virus. [19][20][21][22] However, the potency of mangosteen against SARS-CoV-2 is remains unclear. Therefore, this study aimed to identify the potency of bioactive compounds derived from mangosteen as an antiviral agent via dual inhibitor mechanisms towards two SARS-CoV-2 proteases with in silico approach.…”
Section: Introductionmentioning
confidence: 99%